2000
DOI: 10.1089/ars.2000.2.2-197
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane NADH-Oxidoreductase System: A Critical Review of the Structural and Functional Data

Abstract: The observation in the early 1970s that ferricyanide can replace transferrin as a growth factor highlighted the major role plasma membrane proteins can play within a mammalian cell. Ferricyanide, being impermeant to the cell, was assumed to act at the level of the plasma membrane. Since that time, several enzymes isolated from the plasma membrane have been described, which, using NADH as the intracellular electron donor, are capable of reducing ferricyanide. However, their exact modes of action, and their phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 81 publications
0
41
0
1
Order By: Relevance
“…Although PMOR activity has been associated with many critical cellular functions, such as growth control, apoptosis and bioenergetics, its precise role(s) has been difficult to resolve, possibly due to its overarching role as a redox sensor or as a regulator of the cellular redox environment (Baker and Lawen 2000). Through the transfer of electrons from intracellular NADH to extracellular electron acceptors, including plasma membrane protein disulfides (Morre et al 1998), the PMOR has the ability to regulate both the intracellular (Martinus et al 1993;Larm et al 1994) and plasma membrane redox state to maintain an optimized environment for redox signaling and bioenergetics, both of which play important roles in cellular decisions to live or die (Bowling and Beal 1995;Maher and Schubert 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PMOR activity has been associated with many critical cellular functions, such as growth control, apoptosis and bioenergetics, its precise role(s) has been difficult to resolve, possibly due to its overarching role as a redox sensor or as a regulator of the cellular redox environment (Baker and Lawen 2000). Through the transfer of electrons from intracellular NADH to extracellular electron acceptors, including plasma membrane protein disulfides (Morre et al 1998), the PMOR has the ability to regulate both the intracellular (Martinus et al 1993;Larm et al 1994) and plasma membrane redox state to maintain an optimized environment for redox signaling and bioenergetics, both of which play important roles in cellular decisions to live or die (Bowling and Beal 1995;Maher and Schubert 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the PMOR in q°cells (Larm et al 1994), and other cell lines , causes cell death, highlighting its vital role in redox homeostasis. The PMOR also modulates cellular processes that are redox sensitive, including cell growth, intracellular signaling and apoptosis (reviewed in Baker and Lawen 2000), and it maintains plasma membrane antioxidant systems, preventing oxidative stress-induced cell death (reviewed in Villalba and Navas 2000). Although the PMOR has been extensively studied in non-neuronal cells, to our knowledge, studies of the PMOR in primary CNS neurons have not been reported.…”
mentioning
confidence: 99%
“…The high capacity of proliferating mammalian cells to transfer electrons from cytosolic NADH to extracellular acceptors like oxygen via plasma membrane electron transport [45] [46] is now generally regarded as being via a plasma membrane electron transport chain involving reduced quinones as the transmembrane carrier of electrons and protons [3] [47] [48]. The identification and cloning of the constitutive ENOX1 protein of plants whose proposed function is as a terminal oxidase for the plasma membrane electron transport chain [47] rather than superoxide generation, and as a driver of both cell enlargement and of the biological clock represents an important advance in our understanding of these enzyme proteins of the plasma membrane which have, until recently, been largely ill defined [48].…”
Section: Discussionmentioning
confidence: 99%
“…These systems are linked to several vital cellular functions, including growth control, iron uptake, apoptosis, bioenergetics, transformation, and hormone responses (2,5,28). Some of these roles may be linked to the maintenance of appropriate NAD(P) Ï© /NAD(P)H cytoplasmic ratios.…”
Section: Discussionmentioning
confidence: 99%